(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Ernest MillerHemingway, one of the greatest humanists of the twentieth century Americanfiction, was born in Oak Park, Illinois, on 21st July 1899. Hisfather Dr. Clarence Edmunds Hemingway, who was fond of hunting and fishing, wasa physician and introduced Hemingway to the outdoor life. Hemingway receivedhis primary education from a local school and graduated from Oak Park HighSchool in 1917.